Surface functionalization of polypropylene (PP) by chitosan immobilization to enhance human fibroblasts viability. (June 2020) - Morais, D.S.; Ávila, B.; Lopes, C.; Rodrigues, M.A.; Vaz, F.; Machado, A.V.; Fernandes, M.H.; Guedes, R.M.; Lopes, M.A.
Abstract: Driven by the market demand, several synthetic and natural grafts have been proposed during the last years for tendons regeneration. The synthetic grafts, which present a better mechanical performance than the natural ones, usually fail due to the lack of biocompatibility and bioactivity. Thus, chitosan (Cs) was immobilized on polypropylene (PP) surface, previously activated by plasma treatment, in order to improve the fibroblasts' adhesion and proliferation on it. The Orange II dye method and FTIR-ATR analysis proved the successful Cs immobilization on the PP surface. It was observed by SEM and optical profilometry analysis that the Cs concentration increase leads to a surface roughness (Ra value) increase, as well as to water contact angle (C.A.) decrease at least until 2% (w/V) of Cs. Using the 2% (V/V) Cs solution concentration, according to SEM analysis and resazurin assay, the developed functionalization was well succeeded in improving fibroblasts adhesion and proliferation on PP substrates surface over 7 days of culture. Highlights: PP is a polymer that can be used for tendon repair due to better mechanical performance when compared to natural polymers. To improve PP biocompatibility, chitosan (Cs) was used as a source of amino groups to be grafted on PP substrates. Grafting was done by plasma activation conditions of the substrate followed by diverse immersion parameters on Cs solution. Physicochemical features confirmed grafting optimization. Cell assays showed major improvement on the biocompatibility of the treated PP substrate when compared to the untreated one.